(untitled) (قضايا سياسية, 2024)
The global economy constitutes one of the most important structures and basic pillars on which the global system is based, with its elements, components, and interactions with the various variables surrounding it, whether at the internal or external level. Perhaps the most prominent form of this structure was represented by (globalization) with its elements, variables, goals, and principles calling for... Freedom of trade, free markets, privatization, etc. have existed since the late twentieth century and the establishment of a global order led by the United States of America on the ruins of the end of the Cold War and the disintegration of the (former) Soviet Union. However, the rapid and ambiguous changes that the world is experiencing today have been reflected in the extent of this system’s ability to withstand and face challenges. Or the possibility of important transformations in its main structures, as is the case with the Corona pandemic and its important repercussions at all levels, internally and externally, and at varying levels, which were reflected in the global economy as one of the most important pillars of the global system.